The use of institutional theory in scientific research and related topics: a sample of the world panorama - Carpes, Aleteia de Moura (2015)
Institutional Theory can explain the roles of the institutions in the organization of society, however, its application to the study of organizations is recent. That is why this bibliometric study investigates the publications of this issue and see which are the emerging issues. Therefore, publications were searched in Web of Science based on a study of qualitative and quantitative approach to the analysis of 6,945 studies.The results showed that the theme emerged since 1990 and are included primarily in the management area. Its greatest number of publications was found in Organization Studies, the University System and California, the institution linked to most research.